Strain Engineering to Improve the Electronic and Photocatalytic Properties of the Inorganic Graphenylene Based on SiC - Martins, Nicolas [UNESP]; Laranjeira, J. A.S. [UNESP]; de Azevedo, Sérgio [UNESP]; Sambrano, Julio [UNESP] (American Chemical Society (ACS), 2024)
Computational simulations based on density functional theory (DFT) were carried out to show that biaxial strain (ϵ; −10% to +10%) engineering is a smart choice to modify the main properties of the two-dimensional inorganic graphenylene-like silicon carbide (IGP-SiC). It was demonstrated that the compressive deformation leads to a buckling effect on the IGP-SiC; however, the planar configuration remains along the tensile strain. The IGP-SiC under both compressive (ϵ = 0 to −10%) and tensile (ϵ = 0 to +10%) regimes is thermally stable at 700 K, as unveiled by ab initio molecular dynamics simulations. By assessing the Raman spectrum, the E2g modes are red-shifted with tensile strain, which is similar to the graphene’s tendency. Also, tensile deformation reduces the band gap energy from 3.22 eV (ϵ = 0%) to 2.48 eV (ϵ = +10%), leading the IGP-SiC to a visible-light spectrum. On the other hand, the compressive regime induces an opening of the band-gap energy to 4.05 eV (ϵ = −10%). Other remarkable results for strained IGP-SiC are the photocatalytic properties maintained at biaxial strain because the band edges meet the oxidation and reduction standard potentials, especially for strain regimes from +4% to +10%. Besides this, the IGP-SiC under strain application is a suitable alternative in photocatalytic degradation and water desalination due to its good performance in all pH environments.
Keywords: 2D materials; biphenylene; graphenylene; photocatalysis; SiC; strain